Increase in blood-transferable linear and cyclic dipeptides in human plasma following ingestion of elastin hydrolysate - Yu Iwasaki; Mikako Sato; Yoshinori Katakura; Yukihiro Sugawara; Yasutaka Shigemura (Food Hydrocolloids for Health)
In this study, we analyzed the absorption of linear and cyclic dipeptides containing Gly, Pro, Ala, and Val by human blood following the ingestion of elastin hydrolysate. As in previous studies, Pro-Gly was transferred into blood at the highest concentration (Cmax; 14.63 nmol/mL). Moreover, this is the first study to show that Gly-Pro, Pro-Ala, Gly-Ala, cyclo(Gly-Pro), cyclo(Pro-Ala), cyclo(Pro-Val) and cyclo(Gly-Ala) also increase in blood after the ingestion of elastin hydrolysate. The contents of these cyclic dipeptides, which amounts in elastin hydrolysate is verry small, suggested that elastin digestives may be cyclized during digestion and absorption by human blood following the ingestion of elastin hydrolysate. This study suggested that these blood-transferrable linear and cyclic dipeptides could be candidates for elastin-derived bioactive peptides, and this finding consequently led to the further experiments that has been required for clarifying the bioactivities and mechanisms of beneficial effects of elastin hydrolysate.